RELACJE POMIĘDZY KLEREM UNICKIM I ŁACIŃSKIM W SCHYŁKOWYM OKRESIE UNII W OBWODZIE BIAŁOSTOCKIM - Matus, Irena (Acta Neophilologica, 2018)
In the Republic of Poland, the Uniate clergy was perceived as second-class in comparison to the Latin one. Contrary to expectations, the hierarchy was not made equal to the Roman Catholic clergy. A disastrous economic situation of the non-Latin priests resulted in their low level of education and, what is more, being disrespected. This applied to even well educated and well off Basilians. In the history of the union, the relationships between the clergy of both rites were varied, more ambitious in the case of hierarchy and simpler on the level of parish priesthood. As regards church dignitaries of both rites, the situation became more complicated after the partition of Poland, when the Russian authorities appointed a church board in Petersburg also for the Uniates. The conflicts were caused by imposing Latin control over Uniate matters and converting the Uniates into Roman Catholicism. The situation changed after 1805, when the department board for the Uniate matters was established. From then on, as the reconstitution of Orthodoxy was becoming more obvious, the relationship between the hierarchs of both rites was slackened. However, those between the strongly Latinized and Polonized (cooperating at the parish level) Uniates and Latin clergies in the 1830s were becoming more difficult. In 1835, the conversion into the Latin rite and providing mutual pastoral services were forbidden. The conflicts at the parish level concerned conversions of Greek Catholics and the division of a tithe (the tithe paid by the Uniates was often taken over by the Latin clergy). These conflicts escalated in 1828 when the Senate issued a ruling demanding a return of the tithe to the non-Latin priests. Its implementation was not easy, especially in the Bialystok borderland district. Consequently, special clerical and religious commissions were appointed that separated the tithe for the churches in Siemiatycze and Żurobice. Long-lasting disciplinary proceedings were conducted in the case of the Uniate church in Żerczyce, Mielnik, Ciechanowiec, Brańsk, Boćki and Drohiczyn in the Bielsk district and in Kuźnica in the Białystok district.